Assessing the impact of the coronavirus pandemic on the mental health status of intensive care unit nurses: a systematic review - Peter Onchuru Mokaya; Nancy Ntinyari; Godfrey Limungi; Evans Kiptulon Kasmai; Hideg-Fehér Gabriella (BMC Nursing)
Abstract Introduction The Coronavirus pandemic (COVID-19) was first identified in December 2019 in Wuhan, China, and later caused a severe health crisis, causing massive disruptions to most healthcare systems worldwide. During this pandemic period, the structure of the Intensive Care Unit (ICU) activities changed fast. It was observed that the mental health of ICU nurses reached levels of extreme clinical and psychological concern. This paper aims to shed light on how COVID-19 affected ICU nurses’ mental health. Methods A literature review of articles published on this topic from January 2020 to December 2024. English-language, peer-reviewed, mixed-methods, qualitative, and quantitative research on the mental health outcomes of ICU nurses were included while studies without primary data, non-ICU nurses, and non-peer-reviewed publications were excluded. To identify relevant literature, we searched five databases, including PubMed, MEDLINE, CINAHL, Web of Science, and Embase. Additionally, grey literature sources, including Google Scholar and Research Gate, were also searched. Narrative synthesis was used to evaluate both quantitative and qualitative data. Results A total of 23 articles were reviewed. The most prevalent mental health issues were depression, anxiety, fear, and post-traumatic stress disorder (PTSD). The effects of burnout, illness, exhaustion, physical strain, sleep disturbances, and ongoing job stress were equally detrimental to the health of ICU nurses. The nurses’ health declined as a result of the new procedures and working environment, the enormous workload, the continued exhaustion, the concerns for their families and themselves being infected by COVID-19, the social reaction, and seeing the death toll rise. Conclusion The COVID-19 pandemic had a negative impact on nurses’ mental health well-being such as stress, depression, post-traumatic stress disorder, insomnia, anxiety, and fear. Sustainable support systems, networks and plans ought to be made available. Due to unique working conditions of ICU nurses and in readiness for similar pandemics in future, legislators should focus on the mental health of ICU nurses because they play a critical role in managing public health crises as frontline health solders.